Plasma surfactant protein levels and clinical outcomes in patients with acute lung injury. Issue 11 (29th October 2003) - Eisner, M D; Parsons, P; Matthay, M A; Ware, L; Greene, K
Abstract : Background: Because injury to the alveolar epithelial barrier is a characteristic feature of acute lung injury (ALI) and the acute respiratory distress syndrome (ARDS), plasma surfactant protein levels may have prognostic value. To test this hypothesis plasma surfactant proteins A and D (SP-A and SP-D) levels were measured in patients with ALI or ARDS enrolled in the NHLBI sponsored multicentre ARDS Network randomised controlled trial of a 6 ml/kg v 12 ml/kg tidal volume strategy. Methods: Data from 565 participants in the clinical trial were used. Plasma levels of SP-A and SP-D were measured at baseline and on day 3 after the start of the mechanical ventilation protocol. The longitudinal impact of baseline plasma surfactant protein levels on clinical outcomes was examined by multivariate analysis, controlling for mechanical ventilation group, APACHE III score, and other clinical covariates. The effect of 6 ml/kg tidal volume ventilation on plasma SP-A and SP-D levels was evaluated using analysis of covariance. Results: Baseline plasma SP-A levels were not related to any clinical outcome. In contrast, higher baseline plasma SP-D levels were associated with a greater risk of death (OR 1.21 per 100 ng/ml increment; 95% CI 1.08 to 1.35), fewer ventilator-free days (mean decrease −0.88 days; p=0.001), and fewer organ failure-free days (mean decrease −1.06 days; p<0.0001). The 6 ml/kg tidal volume strategy had no effect on the rise in plasma SP-A levels (p=0.91) but attenuated the rise in plasma SP-D levels (p=0.0006). Conclusions: Early in the course of ALI/ARDS an increased level of plasma SP-D is associated with a worse clinical outcome. The 6 ml/kg tidal volume strategy attenuated the rise of SP-D early in the clinical course. Taken together, these observations indicate that plasma SP-D, a product of alveolar type II cells, is a valuable biomarker in ALI/ARDS.